Perancangan Timing Belt Pada Toyota Fortuner 2014 - David Henock Tampubolon; Ratna Dewi Anjani; Deri Teguh Santoso (Peneliti.net, 2022)
Many people who buy a car don't know how to take care of their car properly. Many of us encounter cases of car accidents or damage due to the owners not knowing how to take care of their car, resulting in an accident or damage due to technical problems with their car. One example of this case is the timing belt break. The timing belt itself has a different role from the Vanbelt, because the components that are moved by the timing belt are directly related to the distribution system, input, and fuel combustion by the piston in the combustion chamber. The conclusion of this research is the use of a timing belt type H with a maximum tension of 14.9 N which can also be estimated that the age of the Timing Belt is 721000 Working Hours before it can be replaced with a new one.